Assessment of maturity during co-composting of penicillin mycelial dreg via fluorescence excitation-emission matrix spectra: Characteristics of chemical and fluorescent parameters of water-extractable organic matter. (July 2016) - Zhang, Shihua; Chen, Zhiqiang; Wen, Qinxue; Ma, Jiangya; He, Zhonghua
Abstract: To investigate characteristics of water-extractable organic matter (WEOM) from different stages and evaluate the maturity for co-composting penicillin mycelial dreg (PMD) via fluorescence regional integration (FRI) of fluorescence excitation-emission matrix (EEM), a pilot-scale co-composting was carried out. The results showed that a classical temperature profile showed and a degradation rate of 98.1% for residual penicillin was obtained on the 6th day. DOC and DOC/DON ratio were in a low level of 4.0 g kg −1 and 3.7, respectively, after the 32nd day. In addition, respirometric rate (SOUR) decreased to 0.87 mg O2  g −1  VS h −1 finally. The EEM showed that the specific Ex/Em peak related to microbial byproduct-like vanished on the 32nd day, while those related to fulvic-like and humic acid-like appearing on the 24th day. The fluorescence regional integration (FRI) results demonstrated that PV, n /PIII, n increased to 3.28 finally, suggesting a desirable maturity for co-composting PMD. The EEM-FRI consequently has the potential for characterizing the WEOM from the co-composting of PMD. Highlights: Residual penicillin decayed with a degradation rate of 98.1% on the 6th day. Biochemical parameters indicated the co-composting endpoint with a stable level. PV, n /PIII, n based on FRI can reflect maturity for co-composting of PMD. EEM-FRI has the potential for characterizing the process of this co-composting.